Analysis of average market and purchase prices for certain fruit species - Lipcsei, József (Studia Mundi – Economica, 2021)
In addition to the optimal use of resources, the profitability of agriculture is affected by weather anomalies and risk-taking with the market. The latter are the most critical factors of effectiveness over which the average producer has no influence. As the majority of Hungarian producers are small and medium-sized holdings, it is essential to examine their market exposure. At the beginning of the agricultural season, the professional journals often publish record yields and top quality, lacking a professional view that reduces the benefits of producers and thus the market price. The aim of the study is to present the economic exposure of farmers by illustrating the pricing practices of the fruit growing sector, including apples, pears, cherries, sour cherries, peaches, apricots, nectarines, plums, currants, raspberries and strawberries. How the average purchase price develops in addition to fixed assets, expenses and ecological[1]economic risk-taking, and how the average market price develops as a result of the margin. How the trade margin evolves and if there is a correlation between the quantity produced and the final price. The benefit of agriculture is often not the benefit of the farmer, because the profit is realized at the trader. The pricing practices of the reviewed period are multiple for some fruit species and exceptionally high for other fruit species. In the examined period of the fruit sector we cannot establish market flexibility and balance in several cases. In conclusion, the producer price comes as the result of the farmer’s work which is not affected by the yield and the market’s demand in several cases. The main reason is not generated in the agricultural production, however, the purpose of this publication is not to investigate this subject.
Keywords: Margin; Average purchase price; Average market price; Yield; Income